Of bombs and belts: Exploring potential ruptures within China's Belt and Road Initiative in Sri Lanka. Issue 3 (20th February 2020) - Ruwanpura, Kanchana N.; Rowe, Peter; Chan, Loritta
Abstract : Recently, much scholarship has been dedicated to exploring China's Belt and Road Initiative (BRI). A majority of this work has focused on global dimensions of the BRI, typically considering notions of a changing geopolitical landscape or South–South cooperation. However, these grand narratives often displace local realities, especially in the arenas of local political conflict and environmental degradation. Using examples from Sri Lanka, we question whether existing BRI narratives adequately and critically consider local politics of place and environmental degradation in a time of global climate change, two unstable fault lines which could hinder China's implementation of the BRI. In this short commentary, we employ the notion of the blank figure, which draws attention to both absences and presence of undetermined factors that suggest existing narratives fail to adequately consider potential ruptures that may compound effects of mega‐infrastructure and associated environmental degradation. Given this, much more localised research concerning the BRI is needed. Abstract : The recent scholarship exploring China's Belt and Road Initiative (BRI) has mainly focused on its global dimensions. However, these grand narratives often displace local realities, especially in the arenas of local political conflict and environmental degradation. Using examples from Sri Lanka, we question whether existing BRI narratives adequately and critically consider local politics of place and environmental degradation in a time of global climate change, two unstable fault lines which could hinder China's implementation of the BRI.